2002
DOI: 10.1017/s0031182002002020
|View full text |Cite
|
Sign up to set email alerts
|

Schistosome genetic diversity: the implications of population structure as detected with microsatellite markers

Abstract: Blood flukes in the genus Schistosoma are important human parasites in tropical regions. A substantial amount of genetic diversity has been described in populations of these parasites using molecular markers. We first consider the extent of genetic variation found in Schistosoma mansoni and some factors that may be contributing to this variation. Recently, though, attempts have been made to analyze not only the genetic diversity but how that diversity is partitioned within natural populations of schistosomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 32 publications
3
72
0
Order By: Relevance
“…Given the occurrence of clonal reproduction in the schistosome life cycle, genetic redundancy is expected and has been reported in numerous field studies (Curtis et al, 2002;Prugnolle et al, 2002Théron et al, 2004). As such, extraction and genotyping of every individual collected would become economically demanding at the risk of little return in novel allele detection.…”
Section: Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the occurrence of clonal reproduction in the schistosome life cycle, genetic redundancy is expected and has been reported in numerous field studies (Curtis et al, 2002;Prugnolle et al, 2002Théron et al, 2004). As such, extraction and genotyping of every individual collected would become economically demanding at the risk of little return in novel allele detection.…”
Section: Genotypingmentioning
confidence: 99%
“…and predicting disease epidemiology. However, few investigations of schistosome genetic diversity have sampled extensively from parasite populations residing in the human host (but see Brouwer et al, 2001;Curtis et al, 2002), with researchers choosing instead to focus on more experimentally tractable sylvatic or domesticated definitive hosts (e.g. Barral et al, 1996;Sire et al, 1999Sire et al, , 2001aSire et al, , 2001bPrugnolle et al, 2002Prugnolle et al, , 2005bThéron et al, 2004;Shrivastava et al, 2005;Agola et al, 2006;Wang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of animal macroparasites (for example, flatworms, nematodes) release their offspring into the environment or multiply within one or more intermediate host species, mostly resulting in high genetic diversity levels similar to those reported in free-living organisms (Bush et al, 2001). It has been suggested that the high genetic diversity of macroparasites within individual hosts may reflect the tendency of these hosts to sample a number of transmission sites (Anderson et al, 1995;Nadler, 1995), thereby becoming 'genetic mixing bowls' for parasite genes (Curtis and Minchella, 2000;Curtis et al, 2002). The result is that parasite offspring are well mixed in the environment and that parasite genetic variation is randomly distributed between hosts (Criscione et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Adult schistosomes reside in the circulatory system of their hosts; therefore, sampling adults from humans is problematic if not impossible. Traditionally, for genetic analysis schistosome adults can be obtained from humans only by hatching eggs from stool samples, using the miracidia to infect snails, the cercariae to infect mice, and collecting the adults from mice via perfusion (Curtis et al, 2001;Curtis et al, 2002;Rodrigues et al, 2002b;Stohler et al, 2004;Agola et al, 2006). This technique has many disadvantages, particularly the introduction of sampling bias through the loss of genotypes by sampling error or selection (Rodrigues et al, 2002a;Stohler et al, 2004;Gower et al, 2007).…”
Section: Introductionmentioning
confidence: 99%